2011
DOI: 10.1007/s13238-011-1047-9
|View full text |Cite
|
Sign up to set email alerts
|

APP and APLP1 are degraded through autophagy in response to proteasome inhibition in neuronal cells

Abstract: Amyloid beta (Aβ) precursor protein (APP) is a key protein in the pathogenesis of Alzheimer's disease (AD). Both APP and its paralogue APLP1 (amyloid beta precursor-like protein 1) have multiple functions in cell adhesion and proliferation. Previously it was thought that autophagy is a novel beta-amyloid peptide (Aβ)-generating pathway activated in AD. However, the protein proteolysis of APLP1 is still largely unknown. The present study shows that APLP1 is rapidly degraded in neuronal cells in response to stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…However, it remains controversial whether full-length APP is processed in autophagy. Recently, it was shown that APP can be found accumulated in autophagic compartments and that APP and its paralogue APLP1 are substrates for autophagy (16,43). It also was found that BEC1 reduces cellular APP levels, and its deficiency alters APP metabolism (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains controversial whether full-length APP is processed in autophagy. Recently, it was shown that APP can be found accumulated in autophagic compartments and that APP and its paralogue APLP1 are substrates for autophagy (16,43). It also was found that BEC1 reduces cellular APP levels, and its deficiency alters APP metabolism (16).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described Zhou et al, 2011aZhou et al, , 2011b, total RNAs were prepared using NucleoSpin® RNA II kit. Expression level of target genes was normalized with GAPDH.…”
Section: Real-time Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…First of all, autophagy is believed to be another major Aβ clearance pathway besides those well-known Aβ degradation enzymes [56]. Autophagy facilitates the degradation and clearance of APP [57] as well as all APP cleavage products including Aβ [47,58], and APP-CTFs (amyloid precursor protein cleaved C-terminal fragment) [59]. In microglia, Aβ has also been found to be degraded by autophagy through the autophagy receptor optineurin [60].…”
Section: Autophagy Dysfunction and Ad-related Pathologymentioning
confidence: 99%